2020
DOI: 10.3390/microorganisms9010024
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Succession through the Artisanal Process and Seasonal Effects Defining Bacterial Communities of Raw-Milk Adobera Cheese Revealed by High Throughput DNA Sequencing

Abstract: The bacterial community of the artisanal Adobera cheese from Los Altos de Jalisco was described through high-throughput sequencing of 16S rRNA gene libraries. Samples were collected in two different seasons (dry and rainy) during four key steps of the manufacturing process (raw milk, fresh curd, matured curd, and cheese). Bacterial diversity was higher in early steps in comparison with the final elaboration stages. Firmicutes and Proteobacteria were the most abundant phyla, strongly represented by the Streptoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 76 publications
2
10
0
Order By: Relevance
“…According to Klaenhammer et al (2002), the main genres of the BAL group present in cheese are Lactococcus, Lactobacillus, Leuconostoc, Enterococcus, and Streptococcus. Concordantly, our results also confirmed the presence of these kinds of microorganisms in samples of fresh artisan cheeses (Ruvalcaba-Gómez et al, 2020;Sánchez-Juanes et al, 2020;Yeluri Jonnala et al, 2018). Some strains were found because of the processing of the raw milk, raw milk from the origin to produce the fresh cheeses.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…According to Klaenhammer et al (2002), the main genres of the BAL group present in cheese are Lactococcus, Lactobacillus, Leuconostoc, Enterococcus, and Streptococcus. Concordantly, our results also confirmed the presence of these kinds of microorganisms in samples of fresh artisan cheeses (Ruvalcaba-Gómez et al, 2020;Sánchez-Juanes et al, 2020;Yeluri Jonnala et al, 2018). Some strains were found because of the processing of the raw milk, raw milk from the origin to produce the fresh cheeses.…”
Section: Discussionsupporting
confidence: 87%
“…Undesirable bacteria, including Pseudomonas spp. and Acinetobacter spp., were also detected in raw milk but almost undetectable at the end of the cheese manufacturing process (Ruvalcaba-Gómez et al, 2020). Similarly, the season for sampling was considered to characterize the artisanal Aro cheese.…”
Section: Introductionmentioning
confidence: 99%
“…Seasonality in the diversity of raw milk microbiota has been widely demonstrated (Kable et al, 2016;Li et al, 2018;Ruvalcaba-Gómez et al, 2020). In a longitudinal study involving 10 dairy farms, Li et al (2018) showed that milk microbial communities sampled throughout 12 mo clustered into 2 groups, one comprising fall and spring, and the other summer and winter samples.…”
Section: Milkingmentioning
confidence: 99%
“…Accordingly, although the abundances of Chitinophaga and Niastella were associated with low humidity, greater temperature and humidity levels generally favored the proliferation of most bacteria (Li et al, 2018). Ruvalcaba-Gómez et al (2020) analyzed the microbial composition of raw milk samples across dry (from November to May) and rainy (from June to October) seasons and found greater abundances of Streptococcaceae and Lactococcus in the dry season, whereas Aeromonadaceae and Acinetobacter were more abundant in the rainy season. Although weather conditions, including temperature and humidity, seem to consistently modulate bacterial groups such as mesophilic or psychrotrophic bacteria, a core microbiota may exist for raw milk.…”
Section: Milkingmentioning
confidence: 99%
See 1 more Smart Citation